Fonoaudiologia e práticas de saúde no SUS: análise da produção científica (1990-2005) - Graner, Ana Regina (2007)
In this work, I made an analysis about tendencies and perspectives of the recent production on fonoaudiologic practices in Public Health. To attend this objective, a research of the bibliographical production, from 1990 up to 2005, of the area was realized (without the pretension of deplete it). The chronological period was defined in function of the fact that in these last 15 years, with de advection of SUS, was an increase of researches, actuations and publications in the public health area, due to the bigger presence and effectiveness of the fonoaudiologic actuation in public health services. For that, was adopted as sources of research, productions elaborated in form of dissertations and/or theses, books and/or chapters and articles in periodicals. The analysis of the data raised, points that the public health is an important area to the Fonoaudiology, an open field to be explored, in actuation and research. If the subject Fonoaudiology and Public Health entered the agenda of actual productions more intensely, then it is necessary greater investments and inquiries by the fonoaudiologics